Influence of Gas Pressure on the Threshold Potential in Hydrogen Sulphate - Prashad, Jagdish (Asian Journal of Chemistry, 2010)
The influence of gas pressure p on the threshold potential Vm has been studied in hydrogen sulphide gas under ozonizer excitation. Vm has been found to increase with p.